Open and standardized tools for smart transducer networking - Rossi, S. R. (2005)
IEEE 1451 Standard is intended to address the smart transducer interfacing problematic in network environments. Usually, proprietary hardware and software is a very efficient solution to in planent the IEEE 1451 normative, although can be expensive and inflexible. In contrast, the use of open and standardized tools for implementing the IEEE 1451 normative is proposed in this paper. Tools such as Java and Phyton programming languages, Linux, programmable logic technology, Personal Computer resources and Ethernet architecture were integrated in order to constructa network node based on the IEEE 1451 standards. The node can be applied in systems based on the client-server communication model The evaluation of the employed tools and expermental results are presented. © 2005 IEEE.